Kajian Paparan dan Risiko 3-MCPDE dan GE dari Produk Formula pada Bayi Usia 0-12 Bulan di Indonesia secara Probabilistik - Wiwi Hartuti; Nuri Andarwulan; Puspo Edi Giriwono (Department of Food Science and Technology (ITP), Faculty of Agricultural Technology, Bogor Agricultural University (IPB) in collaboration with the Indonesian Food and Beverage Association (GAPMMI), the National Agency of Drug and Food Control, and th, 2020)
The 3-monochloropropane-1.2-diol ester (3-MCPDE) and glycidyl ester (GE) are chemical contaminants detected in vegetable oils and food products containing vegetable oils including formula products. This study aimed to assess the exposure and risk of 3-MCPDE and GE from infants formula products in Indonesia. Prediction of 3-MCPDE and GE levels of formula products was carried out probabilistically using data levels of 3-MCPDE and GE vegetable oil. Estimated daily intake (EDI) of 3-MCPDE and GE of formula products were obtained by multiplying the predicted data by consumption data while risk assessment is done by comparing EDI value with toxicology reference value. The predicted values of 3-MCPDE and GE levels of formula products ranged from 213.60-285.65 and 772.89-922.73 μg/kg. The exposure value of 3-MCPDE and GE of formula products based on Individual Food Consumption Survey (IFCS) was 1.53-2.40 and 5.54-7.11 μg/kgbw/day, while based on serving consumption was 3.31-6.68 and 10.88-21.62 μg/kgbw/day. Results of risk assessment indicated that 3-MCPDE was above 100% (health risk) in exception that of the age group 6-12 months based on IFCS with a value of 76.98-84.34%, the average GE with the T25 margin of exposure (MoE) was 1838-471 which was below 25.000. EFSA defined MoE T25 at 25.000 as GE's low risk to health.